Evaluating the effectiveness of mobile-assisted language learning in enhancing English speaking proficiency : A case study in Indonesian high school - Asikin, Muhammad; Rahayu, Endah Yulia; Pramujiono, Agung (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study examines the efficacy of Mobile-Assisted Language Learning (MALL) in improving English speaking skills among Indonesian senior high school students. Employing a mixed-methods approach, the research utilized a quasi-experimental design involving 70 students divided into experimental and control groups. The experimental group utilized mobile applications like ELSA Speak and HelloTalk, whilst the control group implemented conventional ESL methods. Speaking performance was measured through pre-test and post-test scores, complemented by questionnaires and interviews to explore learners’ perceptions.Quantitative findings reveal that although both groups demonstrated statistically significant improvement, the experimental group showed substantially greater gains. The control group recorded a modest mean increase of 1.63 points with a moderate effect size (Cohen’s d = 0.58), whereas the experimental group achieved a remarkable mean gain of 13.23 points, accompanied by a very large effect size (Cohen’s d = 3.36). These results indicate that MALL is considerably more effective than traditional instruction in improving English speaking proficiency. The reduced score variability in the experimental group further suggests more consistent learner achievement following the intervention. Qualitative findings indicate that MALL increased learners’ motivation, reduced speaking anxiety, and enhanced learner autonomy through flexible practice and immediate feedback. Despite its effectiveness, the study identified challenges related to technological constraints and initial instructor readiness. Issues such as unstable internet connectivity occasionally disrupted learning, and limited early guidance affected initial application use. However, these challenges did not significantly hinder learning outcomes when adequate teacher support was provided. Overall, the findings demonstrate that MALL offers a pedagogically effective approach to enhancing English speaking skills in the Indonesian high school context. When integrated thoughtfully with conventional instruction and supported by appropriate technological and instructional preparation, MALL has strong potential to transform speaking instruction and promote more engaging, autonomous, and effective language learning.